2002
DOI: 10.1097/00005768-200204000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Mid-femur geometry and biomechanical properties in 15- to 18-yr-old female athletes

Abstract: Running, a weight-bearing exercise, is associated with more favorable geometric and biomechanical characteristics in relation to bone strength, compared with the weight supported activities of swimming and cycling. Differences may reflect skeletal adaptations to the specific mechanical-loading patterns inherent in these sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
3
51
0
1
Order By: Relevance
“…Myburgh et al (1993) found the greater width of the ulna to be a significant predictor of EI in men who were highly active compared to less or moderately active individuals. Duncan et al (2002aDuncan et al ( , 2002b found the medullary cavity cross-sectional areas in femurs to be wider in athletes exposed to low rather than high-load sports, a structural difference that would enhance the mechanical strength of bone. An increase in bone width is an adaptation in bone remodeling to compensate for mineral loss with age and maintain strength in the human radius (Burr and Martin 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Myburgh et al (1993) found the greater width of the ulna to be a significant predictor of EI in men who were highly active compared to less or moderately active individuals. Duncan et al (2002aDuncan et al ( , 2002b found the medullary cavity cross-sectional areas in femurs to be wider in athletes exposed to low rather than high-load sports, a structural difference that would enhance the mechanical strength of bone. An increase in bone width is an adaptation in bone remodeling to compensate for mineral loss with age and maintain strength in the human radius (Burr and Martin 1983).…”
Section: Discussionmentioning
confidence: 99%
“…4). The total femoral width (TW) and medullar width (MW) were measured at the midshaft [9,18,21,28]. The measurements were taken with fixed visualisation parameters on the PACS-stored images.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical stress is also important in bone modelling and various activities, such as weightbearing exercises, may enhance cortical femur strength [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Weiterhin ist die Belastung der einzelnen Knochenstrukturen stark von der muskulären Stabilisierung abhängig [14,15,21,31,47]. Daher sind Über-lastungsreaktionen nicht selten ein Indiz für Trainingsdefizite.…”
Section: Ergänzende Therapiemaßnahmen Und Prophylaxeunclassified